Peripheral nerve stimulation effectiveness in the upper limb function recovery of patients with a stroke sequel: systematic review and meta-analysis - Obiglio, M; Mendelevich, A; Jeffrey, S; Drault, E; Garcete, A; Kramer, M; Maiaru, M; Modica, M; Ostolaza, M; Peralta, F (Revista de neurologiá, 2016)
In 30-66% of the cases, people who survive a stroke suffer from an affected non functional upper limb. Somatosensory stimulation might positively influence the muscular activity of patients with motor deficiencies caused by a stroke. To carry out a systematic review and a meta-analysis of the effectiveness of peripheral nerve stimulation (PNS) use in the improvement of the plegic/paretic upper limb function in patients with a stroke sequel. Randomized and non randomized clinically controlled tests and crossover studies published until November 2014 in Medline electronic database, Cochrane Central Register of Controlled Trials, LILACS, SciELO and Open Grey were included. Studies at high risk of bias were excluded. Two independent researchers assessed the studies' eligibility criteria and retrieved and analyzed all data. A total of 1,967 studies were found, five of them were included for data retrieval and analysis, using a risk of bias fashion of 6/10 at the PEDro scale. 224 patients were included, 95 of them received PNS in multiple modalities and 129 received other interventions as a control group. The analyzed data suggest that the function of the plegic/paretic upper limb improves after the application of PNS either with or without functional training. On the other hand, the meta-analysis result indicates that there is still insufficient evidence to guarantee the effectiveness of PNS use for the recovery of the plegic/paretic upper limb function in patients with a stroke sequel.